Single-Cell RNA Analysis of Type I Spiral Ganglion Neurons Reveals a Lmx1a Population in the Cochlea - Grandi, Fiorella Carla; De Tomasi, Lara; Mustapha, Mirna (Frontiers in Molecular Neuroscience, 2020)
In the mature cochlea, each inner hair cell is innervated by multiple spiral ganglion neurons of type I (SGNI). SGNIs are morphologically and electro-physiologically diverse. In addition, they differ in their susceptibility to noise insult. However, the molecular underpinnings of their identity and physiological differences remain poorly understood. In this study, we developed a novel triple transgenic mouse, which enabled the isolation of pure populations of SGNIs and analysis of a 96-gene panel via single-cell qPCR. We found three distinct populations of Type I SGNs, which were marked by their exclusive expression of Lmx1a, Slc4a4, or Mfap4/Fzd2, respectively, at postnatal days P3, P8 and P12. Our data suggests that afferent SGN subtypes are established genetically before the onset of hearing, and that the expression of key physiological markers, such as ion channels, is heterogeneous and may be underlying the heterogeneous firing proprieties of SGNIs.